High HIV incidence epidemic among men who have sex with men in china: results from a multi-site cross-sectional study. Issue 1 (December 2016) - Xu, Jun-Jie; Tang, Wei-Ming; Zou, Hua-Chun; Mahapatra, Tanmay; Hu, Qing-Hai; Fu, Geng-Feng; Wang, Zhe; Lu, Lin; Zhuang, Ming-Hua; Chen, Xi; Fu, Ji-Hua; Yu, Yan-Qiu; et al.
Abstract Background Recent upsurge of new HIV infections among men who have sex with men (MSM) is a major concern in China. Paucity of national-level information regarding the burden and predictors of this progressive epidemic of new infections called for a multi-centric, timely and comprehensive investigation. Methods Mixed methods were used to recruit MSM from seven cities in China between 2012 and 2013. Recent and established HIV infections were estimated by Western Blot and BED HIV-1 capture enzyme immunoassay. Syphilis and herpes simplex virus-2 (HSV-2) were also tested. Results A total of 4496 eligible MSM were recruited. The majority was aged ≤35 years (77.5 %), migrants (60.3 %), never married (69.8 %), and played receptive role in anal sex (70.5 %). The HIV prevalence was 9.9 %, and 41.9 % were recently infected, with sensitivity/specificity adjusted HIV incidence of 8.9 (95 %CI : 7.6-10.2)/100 Person-Years. The prevalence of history HSV-2 and syphilis were 12.5 % and 8.5 %, respectively. Recent HIV infection was associated with having multiple male partners (aOR  = 1.4, 95 %CI 1.1-1.9), recreational drug use (aOR  = 2.2, 95 %CI 1.6-3.0), anal bleeding (aOR  = 2.1, 95 %CI 1.4-3.0), syphilis infection (aOR  = 2.8, 95 %CI 1.9-4.3) and history HSV-2 infection (aOR  = 2.3, 95 %CI 1.5-3.3). Conclusion High rate of recent HIV infection is potentially resulting in progressive deterioration of the overall HIV epidemic among MSM in China. Targeted interventions to address high-risk MSM including those having multiple partners, history of recreational drug use and syphilis or HSV-2 infection seemed to be the need of the hour.